Fossils Shed a New Light on the Diversity and Disparity of the Family Limoniidae (Diptera, Nematocera) - Krzemiński, Wiesław (Insects, 2021)
SIMPLE SUMMARY: A new established subfamily (family Limoniidae) from Cretaceous Burmese amber shows a unique reduction of radial veins combined with complete set of medial veins. The discovery of this new subfamily contributes to a better understanding of the diversity and disparity of the family, and is important for further research on the evolution of this group of insects. ABSTRACT: A new subfamily Drinosinae (Diptera, Limoniidae) is established with two fossil genera, Drinosa and Decessia gen. nov. with one new species, Decessia podenasi gen. et sp. nov. from Cretaceous Burmese amber. Additional description of Drinosa prisca is based on new material. A new subfamily shows unique reduction of radial veins combined with complete set of medial veins.